2015
DOI: 10.3109/14764172.2015.1052511
|View full text |Cite
|
Sign up to set email alerts
|

Laser and energy-based devices’ complications in dermatology

Abstract: Laser dermatology is an ever-expanding part of the specialty used extensively for both aesthetic and medical conditions. Advances in laser technology have led to an expansion in the number of devices available, with as a consequence an increase in the total number of complications. Fortunately, the current technology has improved greatly which adds to the safety profile of such devices; nevertheless, thorough knowledge of laser complications and how to avoid them is paramount for any practitioner who uses such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…The corticosteroid showed efficacy decreasing the intensity as well as the extent of PIH 22 . The PIH commonly observed after purpura formation was also more effectively reduced by corticosteroids 16 . The hyperpigmentation from lasers generally decreases over time.…”
Section: Hyperpigmentation and Hypopigmentationmentioning
confidence: 94%
See 4 more Smart Citations
“…The corticosteroid showed efficacy decreasing the intensity as well as the extent of PIH 22 . The PIH commonly observed after purpura formation was also more effectively reduced by corticosteroids 16 . The hyperpigmentation from lasers generally decreases over time.…”
Section: Hyperpigmentation and Hypopigmentationmentioning
confidence: 94%
“…This study concluded that premedication with acyclovir, valacyclovir, or famciclovir for 1 to 2 days before the procedure is advised only for those with a history of HSV 9 . Furthermore, Al‐Niaimi 16 suggests that the risk of scarring is so high in cases of HSV that empiric prophylactic medication is the norm.…”
Section: Infectionmentioning
confidence: 96%
See 3 more Smart Citations